2004
DOI: 10.1111/j.1048-891x.2004.014315.x
|View full text |Cite
|
Sign up to set email alerts
|

Scutellaria barbata D. Don induces c-fos gene expression in human uterine leiomyomal cells by activating beta2-adrenergic receptors

Abstract: Scutellaria barbata D. Don (Lamiaceae; SB) inhibited the growth of uterine leiomyomal (LM) cells with unknown actions. The expression patterns of beta-adrenergic receptors (beta-ARs) in human uterine LM cells and functional coupling to gene expression have also been investigated. Northern blot analysis showed that beta-AR subtypes are expressed at different levels in the uterine LM cells and myometrial smooth muscle cells (SMCs). beta1-AR expression was to be found approximately at the same level in the two ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…(Labiatae). It has been used as a treatment for boils, swollen poison, sore throat and venomous snake bites for thousands of years in China [1]. Modern pharmacological studies have showed that S. barbata (SB) has a wide variety of medical applications due to its antioxidant, anticancer, as well as anti-angiogenic effects, etc.…”
Section: Introductionmentioning
confidence: 99%
“…(Labiatae). It has been used as a treatment for boils, swollen poison, sore throat and venomous snake bites for thousands of years in China [1]. Modern pharmacological studies have showed that S. barbata (SB) has a wide variety of medical applications due to its antioxidant, anticancer, as well as anti-angiogenic effects, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The responses of both normal uterine myometrial SMC and leiomyomal SMCs to SB treatment were analysed. Cell cycle analysis using flow cytometry and Western blotting using antibodies against α-SMA, calponin h1 and the G1 cell-cycle-related gene products, cyclin E, cyclindependent kinase 2 (cdk2) and the cdk inhibitor, p27, clearly showed its effectiveness on anti-growth activity of leiomyomal SMCs (Lee et al, 2004a;Lee et al, 2004b). Recently, it was demonstrated that SB inhibits cell proliferation dependent on an apoptotic response.…”
Section: Introductionmentioning
confidence: 99%
“…Human ULSMC and normal human myometrial smooth muscle cells were used in this study, as isolated and described previously (8,18,19) . Peripheral blood mononuclear cells (PBMCs) were isolated from heparinized venous blood of healthy volunteers by Ficoll‐Paque density gradient centrifugation (20) .…”
Section: Methodsmentioning
confidence: 99%